Modeling and identification of hydraulic servo systems. (3rd July 2018) - Aboelela, Magdy A. S.; Essa, Mohamed El-Sayed M.; Hassan, M. A. Mustafa
Abstract: The goal of this research is to implement a nonlinear simulation model of hydraulic servo system (HSS).The model is based on physical laws as well as experimental identification of piston position. It also presents the tuning of PID/PI controller's parameters using particle swarm optimization technique. The mathematical model includes the most nonlinear effects that are involved in the hydraulic system under study. The dynamics of hydraulic systems are highly nonlinear due to directional change of valve opening, friction forces, and oil compressibility. The model describes the behavior of a servo system BOSCH REXROTH servo valve (4WRSE). It has been developed using MATLAB/SIMULINK. The main objective of the simulation modeling and system identification for electro-hydraulic servo valve is to obtain good performance of its dynamic and nonlinear behavior. The identified model has been found to be a third-order continuous time model. The identification of HSS is performed by using System Identification Toolbox of MATLAB. The obtained results are promising and satisfactory. In addition, the simulation and experimental results have shown the superiority of using PID controller type for requirement of minimum settling time and the PI controller type for minimum value of percentage overshoot.